2014
DOI: 10.4172/2157-7633.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Stem Cell Therapy: Specific Applications in the Treatment of Cutaneous Radiation Syndrome

Abstract: The emergence of stem cell therapy and cellular engineering during the last 10 years has allowed new therapeutic strategies to be considered for the treatment of many wound repair disorders in bones, muscles and skin. The cutaneous radiation syndrome that is often associated with radiation burn may also take advantage of these scientific advances. This syndrome, characterized by inflammatory waves, incomplete wound healing and poor revascularization is the dramatic consequence of local irradiation exposure (ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 156 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…Multiple preclinical models have demonstrated the efficacy of MSC-based treatments for promoting the repair and regeneration of thermal burns and radiation exposure [1823]. These studies have reported more expedient wound closure, decreased incidence of infection, increased vasculogenesis, increased elasticity and reduced scar formation [2426] (Fig. 5).…”
Section: Tissue/organ Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple preclinical models have demonstrated the efficacy of MSC-based treatments for promoting the repair and regeneration of thermal burns and radiation exposure [1823]. These studies have reported more expedient wound closure, decreased incidence of infection, increased vasculogenesis, increased elasticity and reduced scar formation [2426] (Fig. 5).…”
Section: Tissue/organ Injuriesmentioning
confidence: 99%
“…
Fig. 5Treatment of a burn patient with a tissue-engineered bilayer skin substitute [2426] (Courtesy of the Tissue Engineering Centre National University of Malaysia Medical Centre). a Medical team examining the skin substitute; b Fixation of the skin substitute; c One month post-treatment; d Three months post-treatment
Fig.
…”
Section: Tissue/organ Injuriesmentioning
confidence: 99%
“…Skin is the largest organ in the body covering the whole external surface of it and forming about 8% of the total body bulk (1). Skin loss can occur for many reasons; one of the most common reasons is thermal trauma.…”
Section: Introductionmentioning
confidence: 99%
“…These factors possess the ability to trigger a cascade of biological reactions such as cell proliferation and migration, tissue granulation and epithelialization and angiogenesis [8]. As a result, research in this area has been intensified so as to carefully examine the proteomic profile and functional potency of MSC derived CM in order to explore the possibility of its potential use to develop anti-aging therapy [9] [10].…”
Section: Introductionmentioning
confidence: 99%